Financing Strategy for On-Grid Solar PV in Cement & Construction Industry: PT CBS Indonesia Case - Sofyan , Dinda Saphira Nabila; Siahaan , Uke Marius; Rahadi , Raden Aswin (Jurnal Economic Resource, 2024)
In Indonesia, the cement industry plays an important for the development of infrastructure, as this industry keeps expanding along with infrastructure development projects and urban areas. This study analyzes the financing strategy for on-grid solar PV installation with a case study of PT Cibinong Bangun Sarana by using financial feasibility analysis, sensitivity analysis, capital budgeting, and US Index. The results show that an international bank loan with a debt-to-equity ratio of 40%:60% is the most optimal financing strategy. This study provides strategic insights for cement companies in implementing sustainable energy solutions, reducing electricity costs, and improving operational efficiency.